ANALISIS KOMODITAS UNGGULAN SUB SEKTOR PERIKANAN AIR TAWAR KABUPATEN OKU SELATAN (JASEP, 2015)
The objectives of this study are (1) to identify potential commodities in fisheries subsector in Ogan Komering Ulu Selatan District, (2) to determine pattern of leading commodities of fisheries subsector agricultural sector in Ogan Komering Ulu Selatan District. The research done with purposive method. Time series date are used in this study namely data based on production during range time 5 years (2008-2012). The result of analysis that commodity fish were identified as a commodity with a base value of LQ> 1 in Ogan Komering Ulu Selatan, namely fish mas and fish patin .the pattern of economic growth in the fisheries sub-sector according to fish commodities in Ogan Komering Ulu Selatan period 2008-2012 according shift share analysis is relatively faster compared with similar fish commodities at provincial.